Smart city in the context of mapping research fields - Szymańska, Daniela; Lis, Andrzej; Korolko, Michał (Bulletin of Geography. Socio-economic Series, 2025)
The aim of this study is to explore the conceptual structure of the research field as well as compare and contrast it with the findings of previous bibliometric smart city research. The study process has been focused on the following research questions (problems): (1) what are the leading themes in the smart city research field? (2) what are the emerging topics in the smart city research field? (3) what are the similarities and differences with the findings of other bibliometric studies regarding the conceptual structure of the field?